(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Pain assessment and management of patients undergoing open heart surgery, especially those with communication barriers, continue to present challenges to nurses. The present study was undertaken to assess the characteristics of post-operative pain suffered by patients after open-heart surgery during hospital recovery, to find out association between pain score of patients and selected variables and to assess the alleviating factors of pain. The study revealed that there was no significant differences between the pain intensity and sex of the patient, or type of surgery. Seventy percent of patients identified the chest incision as their location of pain. In this study, patients recalled post- operative pain as mild to moderate and pain relief from pain medications was adequate.